The Aesthetic of Rest in the Representation of Azorín’s Small Provincial Towns - Cuvardic García, Dorde (2014)
This article analyzes the aesthetic of rest and small philosophy in Azorín´s work, associated to the representation of the indolent, apathetic towns and cities. The eternal return, as seen from Nietzsche´s pessimistic viewpoint, dominates the temporality of small provincial cities represented in his novels and essays: the notion of Progress has disappeared. Monotonous repetition of the same rites and practices dominates this space. For Azorín, when faced with this nihilistic landscape, subjects with intellectual concerns must find their place in the world through the modest enjoyment of small pleasures, those that arise from objects and everyday experiences, symbols of the “national soul”. This is the action plan of small philosophy. Its literary formulation is channeled through the aesthetic of rest, which describes silence, stillness, the paused pace of activities and steady beat of the bells in these social spaces.